Content Analysis of Work Limitation, Stanford Presenteeism, and Work Instability Questionnaires Using International Classification of Functioning, Disability, and Health and Item Perspective Framework. (28th December 2013) - Arumugam, Vanitha; MacDermid, Joy C.; Grewal, Ruby
Abstract : Background . Presenteeism refers to reduced performance or productivity while at work due to health reasons. WLQ-26, SPS-6, and RA-WIS are the commonly used self-report presenteeism questionnaires. These questionnaires have acceptable psychometric properties but have not been subject to structured content analysis that would define their conceptual basis. Objective . To describe the conceptual basis of the three questionnaires using ICF and IPF and then compare the distribution and content of codes to those on the vocational rehabilitation core set. Methods . Two researchers independently linked the items of the WLQ-26, SPS-6, and RA-WIS to the ICF and IPF following the established linking rules. The percentage agreement on coding was calculated between the researchers. Results . WLQ-26 was linked to 62 ICF codes, SPS-6 was linked to 17 ICF codes, and RA-WIS was linked to 74 ICF codes. Most of these codes belonged to the activity and participation domains. All the concepts were classified by the IPF, and the most were rational appraisals within the social domain. Only 12% of codes of the core set for vocational rehabilitation were used in this study to code these questionnaires. Conclusion . The specific nature of work disability that was included in these three questionnaires was difficult to explain using ICF since many aspects of content were not confined. The core set for vocational rehabilitation covered very limited content of the WLQ-26, SPS-6, and RA-WIS.